Female Identity: A Deconstructive study of “The Adulteress” by Sabyn Javeri - Ayesha Aslam,; Akhtar Ali,; Abdul Sattar, (Al-Qanṭara, 2023)
This paper aims at identifying female identity that is misrepresented in the short story “The Adulteress” by Sabyn Javeri (2019). The third person narrator she in the story is continuously trying to build her identity from the perspective of imaginary male character he. The privileged binary of the Adulteress (Javeri, 2019) is male though it is absent, but its continuous presence is felt in the identity presentation and construction of female. To find out the construction of female identity Feminism (Khaddar, 2018) is used as a theoretical perspective and deconstruction approach of Derrida (Tyson, 2014) is applied as a method to provide true meaning to the representation of female identity in the story. The study is qualitative in nature. The findings have exposed that the binary of male is absent in the story and the male in the story is only imaginary male who is present with her even when she was performing normal chores of daily routine. It seems as if the female identity construction is done from the perspective of male in the selected text, but the deconstruction approach helps in portraying the identity of female that is misrepresented in the story.